Romans exposition of chapter 13 : Life in two kingdoms - Lloyd-Jones, David Martyn 1899-1981 (Edinburgh, Scotland Banner of Truth, 2002)
Sermons originally preached at Westminster Chapel between November 1966 and May 1967.
Keywords: Bible. N.T. Romans XIII -- commentaries